2014
DOI: 10.1299/mej.2014smm0049
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate sensitivity and mechanical anisotropy of selective laser melted 17-4 PH stainless steel

Abstract: Quasi-static and dynamic tensile testing was performed upon machined tensile specimens fabricated from bulk primitives produced by the consolidation of water atomized, 17-4 precipitation hardened stainless steel powder by layer-based, selective laser melting. Such mechanical evaluation was performed by a screw-driven uniaxial tension testing machine and a split-Hopkinson tensile bar apparatus. Strain rates evaluated include 10-3 , 10-1 and 10 3 s-1. Prior to tensile testing, specimens underwent additional ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 6 publications
(2 reference statements)
1
13
0
Order By: Relevance
“…In addition, LBM 17-4PH MSSs has a specific microstructure induced by the process, which leads to morphological texture through the building direction of the parts with a dendritic microstructure. All these particular microstructural features lead to a complex mechanical response with significant differences depending on the loading axis during the mechanical test and the building direction of the as-built parts [15,[19][20][21][22][23][24][25]. Heat treatments performed after the building step can also modify the microstructure; results showed that the solution annealing and ageing heat treatment commonly used for conventional 17-4PH MSS, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LBM 17-4PH MSSs has a specific microstructure induced by the process, which leads to morphological texture through the building direction of the parts with a dendritic microstructure. All these particular microstructural features lead to a complex mechanical response with significant differences depending on the loading axis during the mechanical test and the building direction of the as-built parts [15,[19][20][21][22][23][24][25]. Heat treatments performed after the building step can also modify the microstructure; results showed that the solution annealing and ageing heat treatment commonly used for conventional 17-4PH MSS, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on as-built PH SS AM components revealed a non-equilibrium microstructure, as well as strong differences in texture parallel and perpendicular to the build direction, due to the very high cooling rates [17,99,[104][105][106][107]115]. Some of the literature claimed that the as-built microstructure via L-PBF contains martensite and retained austenite (metastable phase at room temperature) [26,27,95,98,[119][120][121][122], completely different from that of a wrought 17-4 PH stainless steel, which is fully martensitic. However, Alnajjar et al [117] and Sun et al [123] respectively reported a fully δ-ferrite microstructure (based on Figure 2) and a dominantly ferrite microstructure ( Figure 3) with small grains at melt-pool boundaries comprising bcc martensitic laths and equiaxed fcc austenite grains.…”
Section: Microstructure In As L-pbfed Statementioning
confidence: 99%
“…Although 17-4 PH is well suited for production by L-PBF [ 8 ], when produced by this method austenite phase fractions of over 50% have been measured in the as-built structure [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. This large amount of retained austenite leads to inconsistent heat treatment response and reduced strength compared to a traditionally processed martensitic structure [ 13 , 16 , 17 ]. The phenomenon of high retained austenite L-PBF 17-4 PH is well documented and can be primarily attributed to the absorption of austenite stabilizing nitrogen into the material from either the cover gas used in the process or the atomization gas used for powder production [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%